Cross-Talk Between Mesenchymal Stromal Cells (MSCs) and Endothelial Progenitor Cells (EPCs) in Bone Regeneration - Bouland, Cyril; Philippart, Pierre; Dequanter, Didier; Corrillon, Florent; Loeb, Isabelle; Bron, Dominique; Lagneaux, Laurence; Meuleman, Nathalie (Frontiers in Cell and Developmental Biology, 2021)
Bone regeneration is a complex, well-orchestrated process based on the interactions between osteogenesis and angiogenesis, observed in both physiological and pathological situations. However, specific conditions (e.g., bone regeneration in large quantity, immunocompromised regenerative process) require additional support. Tissue engineering offers novel strategies. Bone regeneration requires a cell source, a matrix, growth factors and mechanical stimulation. Regenerative cells, endowed with proliferation and differentiation capacities, aim to recover, maintain, and improve bone functions. Vascularization is mandatory for bone formation, skeletal development, and different osseointegration processes. The latter delivers nutrients, growth factors, oxygen, minerals, etc. The development of mesenchymal stromal cells (MSCs) and endothelial progenitor cells (EPCs) cocultures has shown synergy between the two cell populations. The phenomena of osteogenesis and angiogenesis are intimately intertwined. Thus, cells of the endothelial line indirectly foster osteogenesis, and conversely, MSCs promote angiogenesis through different interaction mechanisms. In addition, various studies have highlighted the importance of the microenvironment via the release of extracellular vesicles (EVs). These EVs stimulate bone regeneration and angiogenesis. In this review, we describe (1) the phenomenon of bone regeneration by different sources of MSCs. We assess (2) the input of EPCs in coculture in bone regeneration and describe their contribution to the osteogenic potential of MSCs. We discuss (3) the interaction mechanisms between MSCs and EPCs in the context of osteogenesis: direct or indirect contact, production of growth factors, and the importance of the microenvironment via the release of EVs.